Effect of concentration of molecular crowder on the unfolding force distribution: emergence of a long tail. (27th March 2017) - Kumar, Sanjiv; Singh, Amit Raj; Giri, Debaprasad; Kumar, Sanjay
Abstract: We investigate the force induced unfolding transitions of a polymer in presence of crowding particles over a wide range of conditions. The polymer conformations are specified by the reaction coordinate i.e. end-to-end distance and the quality of the solvent. Crowding distribution is obtained through the percolation process, which gives rise to a distribution of clusters of different shapes and sizes starting from isolated disorder sites up to clusters with an extent spanning the entire system. It was shown here that the polymer structures are altered by such distributions and induces an array of structural changes in the form of intermediate states. It was found that the mechanical stability of polymer was insensitive at lower concentration, but increases at higher concentration. This is in accordance with experiments. Exact results based on a short polymer revealed that there is emergence of a long tail in the unfolding force distributions. This is less visible at lower concentration, but has significant contribution at higher concentration. This important feature either was overlooked or not explored so far, and therefore, needs further investigation.